2014
DOI: 10.1603/en14131
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of Aphid and Primary Parasitoid Trophic Relations of Genus <I>Alloxysta</I> (Hymenoptera: Cynipoidea: Figitidae: Charipinae)

Abstract: This tutorial demostrates the use of ordination methods in R package vegan. The tutorial assumes familiarity both with R and with community ordination. Package vegan supports all basic ordination methods, including non-metric multidimensional scaling. The constrained ordination methods include constrained analysis of proximities, redundancy analysis and constrained correspondence analysis. Package vegan also has support functions for fitting environmental variables and for ordination graphics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Differences in morphology and distribution of the sensilla may reflect host use in the two studied Alloxysta species. In fact, in A. consobrina , the greater abundance of SB and ST-D, the smaller size of the SP, the shorter ST-A, and even the overall smaller size of the flagellum, compared with A. victrix , may be related with the fact that the latter species is known to attack about 30% more aphid species than A. consobrina and about twice the number of aphid parasitoid species attacked by A. consobrina ( Ferrer-Suay et al. 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in morphology and distribution of the sensilla may reflect host use in the two studied Alloxysta species. In fact, in A. consobrina , the greater abundance of SB and ST-D, the smaller size of the SP, the shorter ST-A, and even the overall smaller size of the flagellum, compared with A. victrix , may be related with the fact that the latter species is known to attack about 30% more aphid species than A. consobrina and about twice the number of aphid parasitoid species attacked by A. consobrina ( Ferrer-Suay et al. 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, despite both species are clearly generalist in both primary and secondary host use ( Ferrer-Suay et al. 2014 ), they show different host range, A. victrix attacking about 30% more aphid species than A. consobrina and doubling the number of aphid parasitoid species attacked by A. consobrina ( Ferrer-Suay et al. 2014 ).…”
mentioning
confidence: 99%
“…DNA analysis of one species group indicated that the latter point of view is incorrect and that Charipinae are more diverse and more specialized (van Veen et al 2003). Until now, only one study (Ferrer-Suay et al 2014f) has investigated the specificity of species of Charipinae, and that study represents the first qualitative analysis of host specificity and host overlap in the subfamily Charipinae. It focused on the cosmopolitan genus Alloxysta, for which many of the hosts are known (Ferrer-Suay et al 2014f).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, only one study (Ferrer-Suay et al 2014f) has investigated the specificity of species of Charipinae, and that study represents the first qualitative analysis of host specificity and host overlap in the subfamily Charipinae. It focused on the cosmopolitan genus Alloxysta, for which many of the hosts are known (Ferrer-Suay et al 2014f). According to this study, within this subfamily, A.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, new trophic relationships are documented for the first time for some species, which considerably improves knowledge of Charipinae hosts. This information is very useful for the analysis of host specialization in this subfamily to augment the most recent publication (Ferrer-Suay et al 2014).…”
Section: Introductionmentioning
confidence: 98%